2004
DOI: 10.1002/ijc.20203
|View full text |Cite
|
Sign up to set email alerts
|

Fertility pattern does not explain social gradient in breast cancer in denmark

Abstract: The present study was undertaken to assess the impact of reproductive behavior on the social class gradient in breast cancer occurrence in Denmark. Objectives were to study whether the gradient across socioeconomic groups could be explained by fertility differences, whether the gradient across educational groups could be explained by fertility differences and whether the effect of socioeconomic group on breast cancer incidence and mortality could be explained by education and vice versa. We studied 674,084 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
43
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 32 publications
5
43
1
3
Order By: Relevance
“…The social inequality at diagnosis observed in our study contrasts with the increasing risk for breast cancer with increasing education (Danø et al, 2003) and occupational group (Dano et al, 2004) in Denmark. It remains unclear whether the reason for the disparity by risk-group is delay in diagnosis or differing biology of cancers in the groups with less education and income compared with more advantaged groups.…”
Section: Discussioncontrasting
confidence: 99%
“…The social inequality at diagnosis observed in our study contrasts with the increasing risk for breast cancer with increasing education (Danø et al, 2003) and occupational group (Dano et al, 2004) in Denmark. It remains unclear whether the reason for the disparity by risk-group is delay in diagnosis or differing biology of cancers in the groups with less education and income compared with more advantaged groups.…”
Section: Discussioncontrasting
confidence: 99%
“…In a NorwegianSwedish study the educational gradient in breast cancer risk could be fully explained by established breast cancer risk factors [16]. On the other hand, in a Danish study, fertility patterns, did not explain the observed social gradient in breast cancer risk [17]. Among factors associated with an increased risk of breast cancer are low parity or nulliparity, high age at first birth, low age at menarche, high age at menopause and alcohol consumption, whereas breastfeeding and physical activity are associated with a decreased risk [18,19].…”
Section: Discussionmentioning
confidence: 73%
“…Our data, however, did not show any important difference in male proportions between the offspring of breast cancer women and offspring of comparison mothers. It has been reported that women with high socioeconomic status have a higher incidence of breast cancer (Danø et al, 2004), while low socioeconomic status has been associated with adverse birth outcome (Luo et al, 2004). We were unable to adjust for socioeconomic status and therefore we may have underestimated the effect of the disease.…”
Section: Discussionmentioning
confidence: 94%